Curing the Infected Wound: Metaphor of State-Owned Enterprises in News Headlines - Muhammad Adam (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
The current condition of Indonesian State Own Enterprises (SOEs) has become the focus of various studies across fields. The studies extend from an economic perspective to legal aspects, but the study to address the SOEs condition from linguistics perspective has been overlooked. On the other hand, the study of conceptual metaphor in media discourse puts little attention on this particular issue, and plenty of studies of conceptual metaphor do not account for the effect of contextual aspects on the additional inferences of metaphor. This study attempts to fill the gaps by examining the news headlines reports on the current conditions of SOEs using metaphorical expressions. It will take a closer look at the conceptual metaphor STATE-OWNED ENTERPRISES ARE PATIENTS in Indonesian news headlines and conducting further investigation on how contextual aspects influence the additional metaphorical inferences. The study is qualitative with purposive sampling method; the data taken are ten news headlines from online media news which discuss the current improvement process and condition of SOEs using metaphorical expressions. Conceptual Metaphor Theory (Lakoff & Johnson, 1980) is the conceptual framework of this study. From ten news headlines analysed, three metaphorical framings to speak about the current condition of SOEs as if SOEs are patient, i.e.: SOEs is a sick patient with particular sickness, the government is a medical practitioner, and after treatment, SOEs is a healthy patient or a dying patient. The underlying conception of STATE-OWN ENTERPRISES ARE PATIENTS implies that there are still plenty outstanding actions to be taken to improve the SOEs' performance, not only to provide remedies but most importantly is to prevent the sickness. Furthermore, additional inferences may emerge from the same metaphorical expressions in a different situational context. The implication is, media or journalists should consider that unintended inferences may arise from a particular metaphorical expression which are not initially meant to.